Comparison of Bod Pod(R) and DXA in female collegiate athletes - Ballard, T. P.; Fafara, L.; Vukovich, M. D. (Medicine & Science in Sports & Exercise, 2004)
Purpose: This study was designed to evaluate the reliability and validity of air displacement plethysmography (ADP) compared with dual energy x-ray absorptiometry (DXA) Hologic QDR 4500A (Waltham, MA) in female collegiate athletes. Methods: Forty-seven females representing various Division II collegiate sports and 24 controls participated in the current study. All women underwent both methods of testing within a 30-min period. Results: Comparison of means indicated that the ADP and DXA are not different when measuring body fat (BF%) in the athletes (ADP = 22.5 +/- 5.5%, DXA = 22.0 +/- 4.7%P = 1.0). Furthermore, this study determined that ADP is a reliable measure of body fat (BF%; r = 0.96, P < 0.001; 0.97, P < 0.001) in collegiate female athletes and nonathletes, respectively. Conclusion: The results from this study indicate that ADP is a valid measure of body composition in female athletes and nonathletes when compared with DXA.